The great Gatsby - Fitzgerald, F. Scott (Francis Scott), 1896-1940 (Fitzgerald, F. Scott (Francis Scott), 1896-1940. Works. 1991., 2018)
Story of the mysteriously wealthy Jay Gatsby and his love for the beautiful Daisy Buchanan, of lavish parties on Long Island at a time when The New York Times noted "gin" was the national drink and sex the national obsession. --From publisher description.